2020
DOI: 10.1016/j.nepr.2020.102864
|View full text |Cite
|
Sign up to set email alerts
|

Simulated electronic health documentation: A cross-sectional exploration of factors influencing nursing students’ intention to use

Abstract: The aim of this study was to investigate factors influencing nursing students' intention to use a simulated webapplication 'Integrated Nursing Education System' for practicing electronic health documentation. The crosssectional study was conducted at a Malaysian University that provides undergraduate nursing degree program. A total of 133 undergraduate nursing students in their year 2 to year 4 of the program were recruited. They had accessed the simulated web-application as part of the teaching-learning activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…1,[4][5][6] Designed to support and improve patient care, electronic health record (EHR) systems enable collection and storage of a patient's health information on a digital medium, and they have become an integral part of modern healthcare. [7][8][9][10][11] Nurses rely on EHR system for a range of procedures such as drug management, clinical monitoring, clinical decision making, as well as patient care. [12][13][14][15] Such systemized collection of health details in a digital format has a huge potential to improve the efficiency and productivity of healthcare workers, ensuring better quality, safer patient care, and reduced costs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,[4][5][6] Designed to support and improve patient care, electronic health record (EHR) systems enable collection and storage of a patient's health information on a digital medium, and they have become an integral part of modern healthcare. [7][8][9][10][11] Nurses rely on EHR system for a range of procedures such as drug management, clinical monitoring, clinical decision making, as well as patient care. [12][13][14][15] Such systemized collection of health details in a digital format has a huge potential to improve the efficiency and productivity of healthcare workers, ensuring better quality, safer patient care, and reduced costs.…”
mentioning
confidence: 99%
“…They are responsible for several duties, including documentation, implementation, evaluation, and coordination of patient care 1,4–6 . Designed to support and improve patient care, electronic health record (EHR) systems enable collection and storage of a patient's health information on a digital medium, and they have become an integral part of modern healthcare 7–11 . Nurses rely on EHR system for a range of procedures such as drug management, clinical monitoring, clinical decision making, as well as patient care 12–15 .…”
mentioning
confidence: 99%
“…Previous studies have shown an empirical relationship between perceived ease of use and attitude 52 , 53 . Despite the adequacy of resources and support, difficulty levels of healthcare technology are essential in determining users' attitudes 54 . In line with DTPB and other studies, the following hypothesis is proposed: H5: Perceived ease of use positively influences MROs' and AMROs' attitudes toward ICD-11.…”
Section: Literature Reviewmentioning
confidence: 99%